Development Standard Measurement Methods Based of WBS for Mechanical and Electrical Work Volumes of Stadium Area of Special State Building with Integrated Design Build Contract to Increase Accuracy of Mechanical and Electrical Work Volumes Measurement - Renti Odor Siahaan; Yusuf Latief (Journal of Social Research, 2023)
The construction of a stadium that has a fairly high level of complexity with the use of an integrated design and build contract demands an acceleration of execution time, the modernization of the job procurement system and easier project delivery. Not a few of these conditions trigger disputes one of the problems that arise due to the absence of standards in determining the calculation of the volume of work which causes different views from various parties regarding the measurement of the volume of work. This study was conducted to compile and develop Standard Measurement Method (SMM) of the volume of mechanical electrical work in the stadium area based on Work Breakdown Structure (WBS) and to model the relationship between the method of measuring the volume of mechanical electrical work on the level of accuracy of calculating the volume of work using Structural equation modeling (SEM). The results of this study are expected to serve as a guide in measuring volume to create a consistent measurement method and produce a measurement method that can be accepted by various parties.